2016
DOI: 10.1002/2016jd025426
|View full text |Cite
|
Sign up to set email alerts
|

Studying the influence of groundwater representations on land surface‐atmosphere feedbacks during the European heat wave in 2003

Abstract: The impact of 3D groundwater dynamics as part of the hydrologic cycle is rarely considered in regional climate simulation experiments. However, there exists a spatial and temporal connection between groundwater and soil moisture near the land surface, which can influence the land surface‐atmosphere feedbacks during heat waves. This study assesses the sensitivity of bedrock‐to‐atmosphere simulations to groundwater representations at the continental scale during the European heat wave 2003 using an integrated fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
127
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(145 citation statements)
references
References 80 publications
7
127
0
Order By: Relevance
“…It is particularly important in the framework of future climate projections, as groundwater, because of its long residence time, could help alleviate the projected aridity increase over land (Berg et al 2016) and the strengthened heat extremes, as reported by Keune et al (2016) based on simulations of the European heat wave in 2003.…”
Section: Resultsmentioning
confidence: 99%
“…It is particularly important in the framework of future climate projections, as groundwater, because of its long residence time, could help alleviate the projected aridity increase over land (Berg et al 2016) and the strengthened heat extremes, as reported by Keune et al (2016) based on simulations of the European heat wave in 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Szilagyi et al () further confirmed the link between groundwater and ET in Nebraska through observational data. In turn, these impacts may propagate into the atmospheric boundary layer, affecting the planetary boundary layer height, air temperature, convective available potential energy, and convection precipitation (e.g., Gilbert et al, ; Keune et al, ; Maxwell et al, ; Rahman et al, ; Rihani et al, ). A growing body of literature also suggests that lateral subsurface flow can substantially enhance the T / ET ratio (Fang et al, ; Maxwell & Condon, ), and this effect becomes slightly more significant for higher model resolutions (Shrestha et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to simulations of regional climate models coupled to traditional LSMs, such a physically based approach shows less sensitivity to uncertainty in the subsurface hydraulic characteristics that could propagate from deep subsurface to free troposphere (Keune et al, 2016), while other physical representations (e.g., parameterizations in evaporation and transpiration, atmospheric boundary layer schemes) could have significant effects on the simulations as well . Therefore, it is of great scientific interest to further develop the integrated models and benchmarks to achieve improved understanding of complex interactions in the fully coupled Earth system.…”
mentioning
confidence: 99%